Postmodernism and Postmodernity (In the Light of the Development of Digital Technologies and the Processes of Individualization) - Pieniążek, Paweł (Hybris, 2023)
The aim of the article is to confront postmodernism understood as a philosophical doctrine, or, more broadly, a certain type of cultural awareness with postmodernity as an epoch expressing the changes of late capitalism. The relationships between postmodernism and postmodernity are analysed from a philosophical and sociological perspective by comparing the diagnoses of postmodern changes presented by sociologists and the diagnoses presented by representatives of postmodernism. In the first part, I discuss the importance of digital technologies, in which postmodernists hoped to unleash the potential of human creativity, and in the second, the postmodern processes of individualization related to the idea of ​​self-realisation. Finally, I reach the conclusion that postmodernity has betrayed the ideas of freedom, creativity, self-realisation and solidarity proclaimed by postmodernists which, according to their hopes, postmodernity was supposed to realise.